Development of cobalt (Co)-doped monetites for bone regeneration - de Almeida, Gerson Santos [UNESP]; Ferreira, Marcel Rodrigues [UNESP]; da Costa Fernandes, Célio Junior [UNESP]; Suter, Luísa Camilo [UNESP]; Carra, Maria Gabriela Jacheto [UNESP]; Correa, Diego Rafael Nespeque [UNESP]; Rangel, Elidiane Cipriano [UNESP]; Saeki, Margarida Juri [UNESP]; Zambuzzi, Willian Fernando [UNESP] (Wiley, 2024)
Cobalt-doped monetite powders were synthesized by coprecipitation method under a cobalt nominal content between 2 and 20 mol % of total cation. Structural characterization of samples was performed by using X-ray diffraction (XRD), Fourier transform infrared spectroscopy, scanning electron microscopy, and energy dispersive X-ray spectroscopy. XRD results indicated that the Co-doped samples exhibited a monetite single-phase with the cell parameters and crystallite size dependent on the amount of substitutional element incorporated into the triclinic crystalline structure. Cell viability and adhesion assays using pre-osteoblastic cells showed there is no toxicity and the RTqPCR analysis showed significant differences in the expression for osteoblastic phenotype genes, showing a potential material for the bone regeneration.
Keywords: bioactive; bioceramics; bioengineering; biomaterial; tissue regeneration